2020
DOI: 10.7717/peerj.9090
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease, a potential risk factor of non-specific ST-T segment changes: data from a cross-sectional study

Abstract: Background Non-specific ST-T segment changes are prevalent and are proven risk factors for early onset of cardiovascular diseases. They can increase all-cause mortality by 100∼200% and are candidate for early signs of cardiovascular changes. Nonalcoholic fatty liver disease (NAFLD) is prevalent worldwide and is one facet of a multisystem disease that confers substantial increases morbidity and mortality of nonalcoholic fatty liver-related cardiovascular diseases. It is unclear whether NAFLD is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Age, disease duration, ANA titer, and disease activity (SLEDAI-2K) were consistently important factors for 3 major EKG abnormalities in the study cohort. As disease duration is related to age, this factor has been reported to increase the risk of nonspecific ST-T changes by 5.8% in the general population, with an odds ratio [OR] of 1.058 (95% confidence interval [95% CI] 1.052-1.064) previously reported in a large-scale Chinese population study by Xiao et al (41). Another Chinese populationbased study indicated that increasing age (after 35 years old) is a strong risk factor for QT interval prolongation (OR 1.228 [95% CI 1.168-1.290]) (42).…”
Section: Discussionmentioning
confidence: 97%
“…Age, disease duration, ANA titer, and disease activity (SLEDAI-2K) were consistently important factors for 3 major EKG abnormalities in the study cohort. As disease duration is related to age, this factor has been reported to increase the risk of nonspecific ST-T changes by 5.8% in the general population, with an odds ratio [OR] of 1.058 (95% confidence interval [95% CI] 1.052-1.064) previously reported in a large-scale Chinese population study by Xiao et al (41). Another Chinese populationbased study indicated that increasing age (after 35 years old) is a strong risk factor for QT interval prolongation (OR 1.228 [95% CI 1.168-1.290]) (42).…”
Section: Discussionmentioning
confidence: 97%